An Examination of How the Availability of State-backed Terrorism Insurance Programs and Commercial Terrorism Insurance Affects the Operational Decisions of Multinational Companies. - GREY, William / WJG (2011)
This dissertation explores the extent to which the operational decisions of multinational companies (MNCs) are affected by the availability of State-backed terrorism insurance programs and commercial terrorism insurance. The initial hypothesis made is that MNCs will be reluctant to invest in zones or countries with high terrorism or political risks, especially when insurance for these risks may be limited or unavailable. This investigation finds that the availability of State-backed terrorism insurance has a positive impact on MNCs’ demand for terrorism insurance, but that this effect is industry-specific. However, this investigation also found that the operational decisions of large, diversified MNCs are not significantly affected by the availability and scope of coverage of commercial terrorism insurance, although the extent to which this is true also varies by industry, the nature of an MNC’s investments, the location of a business, an MNC’s managerial attitude towards risk, and recent terrorism events. This study also investigates whether insurers can be induced to insure against losses caused indirectly by acts of terrorism or the threat thereof. This investigation found that some insurers already provide this form of coverage but that these products have not proved to be in great demand, as MNCs currently do not appear to be concerned about the indirect financial effects of terrorism or the threat of terrorism. However, in order to assess the full extent to which the operational decisions of MNCs are affected by the availability of State-backed terrorism insurance programs and commercial terrorism insurance further study will be required.